Perceptions of asset managers on corporate social responsibility challenges and opportunities - Kara Nel; Pierre D. Erasmus; Nadia Mans-Kemp (South African Journal of Business Management)
Purpose: Companies and investors in South Africa are challenged with multiple sustainability concerns. Asset managers have substantial power to motivate investee companies to focus on pressing corporate social responsibility (CSR) issues. Yet, there is limited scholarly evidence on how they process CSR information and which sustainability considerations influence their decisions. Therefore, the CSR challenges and opportunities that selected South African asset managers experience were explored.